Estimation of German KIR Allele Group Haplotype Frequencies - Solloch, Ute V.; Schefzyk, Daniel; Schäfer, Gesine; Massalski, Carolin; Kohler, Maja; Pruschke, Jens; Heidl, Annett; Schetelig, Johannes; Schmidt, Alexander H.; Lange, Vinzenz; Sauter, Jürgen (Frontiers in Immunology, 2020)
The impact of the highly polymorphic Killer-cell immunoglobulin-like receptor (KIR) gene cluster on the outcome of hematopoietic stem cell transplantation (HCST) is subject of current research. To further understand the involvement of this gene family into Natural Killer (NK) cell-mediated graft-versus-leukemia reactions, knowledge of haplotype structures and allelic linkage is of importance. In this analysis, we estimate population-specific KIR haplotype frequencies at allelic resolution in a cohort of n=458 German families. We addressed the polymorphism of the KIR gene complex and phasing ambiguities by a combined approach. Haplotype inference within first-degree family relations allowed us to limit the number of possible diplotypes. Structural restriction to a pattern set of 92 previously described KIR copy number haplotypes further reduced ambiguities. KIR haplotype frequency estimation was finally accomplished by means of an expectation-maximization algorithm. Applying a resolution threshold of 1/2n, we were able to identify a set of 551 KIR allele-level haplotypes, representing 21 KIR copy number haplotypes. The haplotype frequencies allow studying linkage disequilibrium in two-locus as well as in multi-locus analyses. Our study reveals associations between KIR haplotype structures and allele frequencies, thereby broadening our understanding of the KIR gene complex.